Reassessing HIV Detection Strategies: An Analysis of Opportunistic Screening vs. Indicator-Condition-Driven Diagnosis in Valencia, Spain. - Ortega, Enrique; Ocete, María Dolores; Martínez-Roma, María; Gimeno, Concepción; Gómez, Neus; Diago, Moisés; Carrodeguas, Alba; Medina, Diogo; García-Deltoro, Miguel (Journal of Community Health, 2024)
Our study assessed the characteristics of people living with HIV (PLWH) detected via opportunistic screening in Valencia (Spain) to determine diagnoses potentially missed under a more restrictive, indicator-condition diagnostic strategy. We conducted a retrospective analysis of electronic health records of 97 PLWH diagnosed between April 2019 and August 2022. The main outcomes reported were patient CD4 T cell count, known HIV risk factors at diagnosis, and missed opportunities for diagnosis, defined as the failure of a previously untested patient to undergo HIV testing despite attending previous visits to healthcare facilities prior to diagnosis. Successful linkage to care was achieved for 95.9% of diagnosed patients. Half of the PLWH were diagnosed late, while 47.8% did not meet the criteria for indicator-condition-driven HIV diagnosis at the time of their diagnosis. Additionally, 52.2% did not receive HIV testing despite an average of 5.1 ± 6.0 healthcare visits in the 12 months prior to diagnosis. Spaniards had more missed opportunities for diagnosis than foreigners (64% vs. 40%, p = 0.02). Depending solely on an indicator-condition-driven HIV diagnosis approach could result in 47.8% of cases being missed. Including "migrants" as a testing criterion could lower missed diagnoses to 25.3% but might create inequities in prevention access. In conclusion, our findings provide valuable insights to enhance HIV testing, early diagnosis, and linkage to care. While it is crucial to uphold the indicator-condition-driven HIV diagnosis as baseline practice, improving screening strategies will decrease late diagnoses and missed opportunities, thereby effectively contributing to end the epidemic.